Two new marine nematode species of the family Comesomatidae Filipjev, 1918 (Nematoda: Chromadorida) from Ha Long Bay, Vietnam - Tu, Nguyen Dinh; Thanh, Nguyen Vu; Smol, Nic; Vanreusel, Ann (Academia Journal of Biology, 2014)
Two new marine nematode species of the family Comesomatidae Filipjev, 1918 (Nematoda: Chromadorida) from Ha Long Bay, Vietnam